If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 109 + -37x Solving 13 + -9x = 109 + -37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37x' to each side of the equation. 13 + -9x + 37x = 109 + -37x + 37x Combine like terms: -9x + 37x = 28x 13 + 28x = 109 + -37x + 37x Combine like terms: -37x + 37x = 0 13 + 28x = 109 + 0 13 + 28x = 109 Add '-13' to each side of the equation. 13 + -13 + 28x = 109 + -13 Combine like terms: 13 + -13 = 0 0 + 28x = 109 + -13 28x = 109 + -13 Combine like terms: 109 + -13 = 96 28x = 96 Divide each side by '28'. x = 3.428571429 Simplifying x = 3.428571429
| 8n=7n+20 | | 30-x+4x-6+2x+10=180 | | 5(5x-1)=37 | | d-9=-8 | | n(n+3)=70 | | 22x+25=47 | | 9(z-6)=4(z+4) | | -6c+8(2c+4)=72 | | 6y+y=-7 | | k^2+4k+4=16 | | 10z=-80 | | 4x-2y=2 | | 3+4(y-2)=31 | | 5-28x=1 | | 4X+1=x-39 | | -3z=48 | | 2x^2-8x+13=0 | | 4.5+0.75= | | 2(9s+3)=6(2s+1) | | 9x=8x-24 | | 3z-9z=24 | | 5(r+6)=4(z+4) | | 5(2x+8)=10 | | -(4y+2)-(-3y-6)=-2 | | 14-5n=-31 | | 55-3x=6x+20 | | 8=-9 | | 6.4m-1.7=14.3 | | 7x-85=4x+3 | | x(x+12)=0 | | 6-(4x+2)=6x-56 | | d-8=-12 |